Clinical frailty and triggers in Takotsubo syndrome: the notable role of a new classification. Issue 2 (February 2020) - Biccirè, Flavio G.; Pannarale, Giuseppe; Acconcia, Maria C.; Torromeo, Concetta; Cardillo, Ilaria; Chianta, Vania; Ferrari, Ilaria; Gaudio, Carlo; Barillà, Francesco
Abstract : Aims: Takotsubo syndrome (TTS) is a mainly transient and acute heart failure mimicking an acute coronary syndrome. Originally described in postmenopausal women, over time TTS has been associated with an increasingly advanced age. Emotional and physical triggers precipitating TTS have been correlated in most cases. The aim of our work was to detect differences between patients with or without recognizable triggers preceding the onset of symptoms. Methods: We enrolled 22 consecutive patients. They were all women with an average age of 71 ± 12 (range 40–90) years. Twelve patients correlated the onset of TTS symptoms with a trigger (group 1) and 10 patients (group 2) denied any correlation with stressful events. Results: Patients in group 1 showed a higher average age than group 2 (76 ± 10 vs. 64 ± 12 years; P = 0.023), a longer hospitalization period (22 ± 12 vs. 11 ± 10 days; P = 0.01) and greater value of frailty score ( P = 0.004). Despite a decrease and subsequent recovery of systolic function, there was no significant difference between groups. Group 1 showed a longer corrected QT (QTc) (505 ± 53 vs. 453 ± 42 ms, P = 0.03), a greater decrease in QTc at discharge (−57 ± 44 vs. 0.3 ± 39 ms; P = 0.004), with the result that at discharge both groups showed a comparable QTc. Conclusion: Our results emphasized that typical TTS female patients with precipitating triggers have advanced age, clinical frailty and QTc abnormalities.